Small GTPase Rab7-mediated FgAtg9 trafficking is essential for autophagy-dependent development and pathogenicity in Fusarium graminearum - Zheng, Huawei (PLoS Genet, 2018)
Fusarium graminearum is a fungal pathogen that causes Fusarium head blight (FHB) in wheat and barley. Autophagy is a highly conserved vacuolar degradation pathway essential for cellular homeostasis in which Atg9 serves as a multispanning membrane protein important for generating membranes for the formation of phagophore assembly site. However, the mechanism of autophagy or autophagosome formation in phytopathogens awaits further clarifications. In this study, we identified and characterized the Atg9 homolog (FgAtg9) in F. graminearum by live cell imaging, biochemical and genetic analyses. We find that GFP-FgAtg9 localizes to late endosomes and trans-Golgi network under both nutrient-rich and nitrogen starvation conditions and also show its dynamic actin-dependent trafficking in the cell. Further targeted gene deletion of FgATG9 demonstrates that it is important for growth, aerial hyphae development, and pathogenicity in F. graminearum. Furthermore, the deletion mutant (ΔFgatg9) shows severe defects in autophagy and lipid metabolism in response to carbon starvation. Interestingly, small GTPase FgRab7 is found to be required for the dynamic trafficking of FgAtg9, and co-immunoprecipitation (Co-IP) assays show that FgAtg9 associates with FgRab7 in vivo. Finally, heterologous complementation assay shows that Atg9 is functionally conserved in F. graminearum and Magnaporthe oryzae. Taken together, we conclude that FgAtg9 is essential for autophagy-dependent development and pathogenicity of F. graminearum, which may be regulated by the small GTPase FgRab7.